2021
DOI: 10.3892/ijo.2021.5276
|View full text |Cite
|
Sign up to set email alerts
|

KDM5B protein expressed in viable and fertile ΔARID mice exhibit no demethylase activity

Abstract: Post-translational modification of histones serve a crucial role in the control of gene transcription. Trimethylation of lysine 4 on histone 3 is associated with transcription activation. There are currently six known methylases and six known demethylases that can control the methylation status of this site. Lysine demethylase 5B (KDM5B) is one such demethylase, which can repress gene expression. In particular KDM5B has been found to be overexpressed in a number of cancer types, and small-molecular weight inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…However, there is agreement that the PHD1 domain can influence the re-modelling of the catalytic core by binding to H3K4me0 [ 15 , 19 , 161 ]. Our own data from the ΔARID mouse expressing KDM5B with a deletion of the ARID domain, together with five amino acids from the JmjN domain (but with the PHD1 intact), show that this mutant has lost demethylase activity [ 85 , 86 ]. However, the fact that the ΔARID mouse is viable and fertile indicates that domains other than the demethylase activity are important in development and viability (See Table 2 and below).…”
Section: Regulation Of Methylation Of Lysine 4 On Histonementioning
confidence: 99%
See 2 more Smart Citations
“…However, there is agreement that the PHD1 domain can influence the re-modelling of the catalytic core by binding to H3K4me0 [ 15 , 19 , 161 ]. Our own data from the ΔARID mouse expressing KDM5B with a deletion of the ARID domain, together with five amino acids from the JmjN domain (but with the PHD1 intact), show that this mutant has lost demethylase activity [ 85 , 86 ]. However, the fact that the ΔARID mouse is viable and fertile indicates that domains other than the demethylase activity are important in development and viability (See Table 2 and below).…”
Section: Regulation Of Methylation Of Lysine 4 On Histonementioning
confidence: 99%
“…Different phenotypes have been reported for KO of KDM5B in C57Bl/6 with Catchpole et al reporting early embryonic lethality [ 85 ], and Albert et al finding perinatal death due to respiratory failure, resulting from neurological abnormalities [ 166 ]. Since the ΔARID mouse, expressing a demethylase null mutant of KDM5B, is viable and fertile [ 85 , 86 ], it follows that functions other than demethylase activity are important in development. The ΔARID mouse provides an appropriate model for examining the effect of the loss of KDM5B enzyme activity on neural activity and behaviour.…”
Section: Regulation Of Methylation Of Lysine 4 On Histonementioning
confidence: 99%
See 1 more Smart Citation
“…Since the protein is correctly localized to the nucleus, questions arise about its biological roles. Recently, Taylor-Papadimitru et al [ 44 ] studied a strain of mice expressing a KDM5B splicing variant that lacked the ARID domain and five amino acids in the JmjN domain. They demonstrated that, although the protein is catalytically inactive, the mouse is viable and fertile, contrary to the KDM5B knockout mouse, which displays an embryonic lethal phenotype [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to full-length KDM5A, ARID-deficient KDM5A exhibits reduced demethylation capacity of H3K4me3 possibly because this mutation alters spatial arrangements or global folding [ 66 ]. Molecular dynamics simulations reveal that the JmjC domain of ARID-deficient KDM5B is more flexible and can induce protein structure dynamic changes compared to full-length KDM5B [ 67 ]. Additionally, KDM5A achieves transcriptional regulation of specific genes through the binding of ARID to the CCGCCC motif [ 66 ].…”
Section: The Structures and Biology Of Kdm5 Familymentioning
confidence: 99%